The impact of the colonial legacy on music performance, focusing on the Zimbabwe Republic Police Band. - Manyame, Patson (Midlands State University, 2017)
It is undoubtedly that colonialism had a dominant and long-lasting impact on Africa hence it has continued to draw a lot of scholarly attention. The research’s main objective was to explore the impact of the colonial legacy on music performance and used the Zimbabwe Republic Police (ZRP) Band as a case study. The research gives a brief summary of the history of the band because its performance can neither be explained nor understood without first unravelling the historical context. The theoretical framework which informs the study is based on Modernisation and African Renaissance theories of development. To collect data, the researcher used interview, questionnaires, and observation. The researcher used stratified sampling procedure to add some boundaries to the process of selection and to apply the principle of randomness within these boundaries. Purposive sampling was also used to bring in people who are critical informants into the research. Results from the study reveal that the colonial legacies are still held important in the band and used to enhance skills development of singers and instrumentalists. On the other hand the findings realised that over reliance on some the colonial legacies has a likelihood of creating a strait jackets in the performance of the band. The study recommends the ZRP band to relinquish irrelevant colonial legacies like the playing of European calls at Police ceremonial events in order to suit contemporary music performances and African contexts. The research also recommended the band to reorient the prevailing music instructional methods such that African methods of learning music can become part of the training process.